Which factors are associated with bone marrow oedema suspicious of axial spondyloarthritis as detected by MRI in the sacroiliac joints and the spine in the general population?. Issue 4 (25th November 2020) - Baraliakos, Xenofon; Richter, Adrian; Feldmann, Daniel; Ott, Anne; Buelow, Robin; Schmidt, Carsten O; Braun, Juergen
Abstract : Objective: Identify factors associated with presence and extension of spinal and sacroiliac joints (SIJ)–MRI lesions suggestive of axial spondyloarthritis (axSpA) in a population-based cohort (Study of Health in Pomerania) aged <45 years. Methods: Spinal (sagittal T1/T2) and SIJ (semicoronal STIR sequences) MRIs were evaluated by two trained blinded readers. The presence (yes/no) and extension (Berlin MRI Score) of bone marrow oedema (BME) were captured. Degenerative spinal lesions were excluded and discrepancies resolved by consensus. Cross-sectional associations between clinical factors and presence/extension of BME were analysed by logistic/negative binomial regression. Record linkage of claims data was applied to identify participants with axSpA. Results: MRIs of 793 volunteers were evaluated. The presence of SIJ–BME (odds ratio) was strongly associated delivery during the last year (4.47, 1.49–13.41). For SIJ–BME extension, associations (incidence rate ratios, 95% CI) were found for delivery ((during last year) 4.52, 1.48–13.84), human leucocyte antigen (HLA)-B27+ (2.32, 1.30–4.14), body mass index (25–30 vs <25 kg/m²; 1.86 (1.19–2.89)) and back pain ((last 3 months) 1.55, 1.04–2.31), while for spinal BME, associations were found for age per decade (1.46, 1.13–1.90) and physically demanding work (1.46, 1.06–2.00). Record linkage was available for 694 (87.5%) participants and 9/694 (1.3%) had a record of axSpA (ICD M45.09). Conclusion: These population-based data support the hypothesis of mechanic strain contributing to BME in the general population aged <45 years and the role of HLA-B27+ as a severity rather than a susceptibility factor for SIJ–BME.